The UAE’s Strategy to Improve the Attractiveness of the Investment Climate - Mehadjebia, Nassira; Halimi, Leila; Mekerkeb, Aberrane Tayeb (Technium Social Sciences Journal, 2023)
This study aims to shed light on the experience of the UAE in attracting foreign direct investment, due to the great and impressive success achieved by the country in terms of preparing for an attractive investment climate for investors, as it was able to compete with developed countries in many fields, so we will focus in this study on a good reading of the investment strategy and policy followed and we will also address its classification in some qualitative and quantitative indicators that directly and indirectly affect the investment decision of the foreign investor, and then a stage will be presented Evaluation of the overall result of investment flows in the UAE.